THE ROLE OF TRANSLATION IN CROSS-CULTURAL COMMUNICATION - Аkramova Dilnoza, Chirchik Stаtе Pеdаgоgicаl Univеrsity Tоurism fаculty Fоrеign lаnguаgе аnd litеrаturе:Еnglish. Sciеntific supеrvisоr: Xamitov Eldor Еnglish tеаchеr, Chirchik Stаtе Pеdаgоgicаl Univеrsity. (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Translation is a cornerstone of cross-cultural communication, enabling the exchange of ideas, knowledge, and values between people of different linguistic and cultural backgrounds. As globalization increases, the need for effective communication across cultures has never been more important. This article explores the significance of translation in facilitating cross-cultural communication, examining its importance in various fields such as diplomacy, business, literature, and humanitarian work. It also delves into the challenges faced by translators in ensuring cultural accuracy and meaning. Additionally, the article considers the evolution of translation with technological advancements and highlights the ongoing role of professional translators in maintaining the integrity of communication between cultures. Ultimately, translation is not only about language conversion but also about fostering understanding and cooperation across borders.